Performance of Cross Listed Dual-Class Firms: Evidence from Chinese Firms Cross Listed on US Exchanges. Issue 15 (8th December 2018) - Abdullah,; Zhou, Jia'nan; Shah, Muhammad Hashim
ABSTRACT: We compare operating and market performance of Chinese single- and dual-class firms cross listed on US exchanges. We find evidence in line with researchers who argue that a dual-class structure allows insiders to invest in long-term value-enhancing projects. We find that dual-class firms underperform prior to their initial public offering (IPO) and then improve and have better operating performance than single-class firms in the second year after IPO. We find that dual-class firms also have better market performance than single-class firms beginning in the initial year, which is contrary to the finding in most other studies. The reason for this might be that firms that list on US exchanges show a credible commitment to shareholder rights.